The Effectiveness of A Proposed Unit Based on Future Problem- Solving Skills in Developing Decision- Making Skills among Government Secondary School Students in Riyadh - Alkhudair, Amal Abdullah Abdulrhman; Abanmi, Alaa Abdulaziz Abdulrhman (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to determine the effectiveness of a proposed unit based on future problem- solving skills in developing the decision- making skills of government secondary school students in Riyadh. Using the descriptive and experimental approach, the tool was to test decision- making skills. Teacher manual; For the Occupational Problems Unit in the Work Environment. They were applied to a multi- stage randomized manner of 63 female students of the third year of secondary school, which was divided into: a control group that the occupational problems unit is taught in the work environment in the traditional way, and an experimental group that is taught using the occupational problems unit in the work environment based on problem- solving skills Future. The research found the effectiveness of the occupational problems unit in the work environment based on future problem- solving skills in developing decision- making skills as a whole. Where the experimental got a total mean (28.77 of 32) in contrast to the control obtaining a total mean (13.05 of 32) and the difference in favor of the experimental group, and the presence of statistically significant differences at a significance level (0.05) between the mean scores of the two groups, the experimental and the control in The post- test in decision- making skills as a whole in the vocational education course and the ETA square factor to measure the size of the effect was (0.97), and confirms that the size of the effect is (large), and the adjusted gain rate for Blake is (1.32), and reflects the great effectiveness of the proposed unit: the researcher recommends directing the curriculum officials in the Ministry of Education to take care of the development of future problem solving skills through the curriculum for their effectiveness in helping students to make decisions and benefiting from the flexibility of the vocational education curriculum in achieving future goals that help students identify their paths Professional.